(3eTGcd eUQ GdeYGUQIs - (3YHO GdYRjR(B, (3GdTQHjfjs ((3GdbGgQI(B:s (3OGQ ZQjH ddfTQ hGdJhRjY(B,s, 1998)
(3cJGHGJ aj GdEOGQI(B- (3cJGHGJ aj GdJShjb hGdJUOjQ(B- (3cJGHGJ aj GdejRI GdJfGaSjI hGdUhQI GdPgfjI ddCee(B- (3cJGHGJ aj GdEbJUGO(B- (3cJGHGJ aj GdYeGdI hGdHWGdI hGdeTcdI GdScGfjI(B.s
Keywords: (3GdeTGcd GdeYGUQIs; (3GdeTcdGJ GdEbJUGOjIs; (3eTGcd eUQs